Elevated Levels of IL-10 and G-CSF Associated with Asymptomatic Malaria in Pregnant Women - Nana O. Wilson; Tameka Bythwood; Wesley Solomon; Pauline Jolly; Nelly Yatich; Yi Jiang; Faisal Shuaib; Andrew A. Adjei; Winston Anderson; Jonathan K. Stiles (Hindawi Limited, 2010)
In sub-Saharan Africa, approximately 30 million pregnant women are at risk of contracting malaria annually. Nearly 36% of healthy pregnant women receiving routine antenatal care tested positive for Plasmodium falciparum HRP-II antigen in Ghana. We tested the hypothesis that asymptomatic HRP II positive pregnant women expressed a unique Th1 and Th2 phenotype that differs from healthy controls. Plasma from healthy (n=15) and asymptomatic (n=25) pregnant women were evaluated for 27 biomarkers (IL-1b, IL-1ra, IL-2, IL-4, IL-5, IL-6, IL-7, IL-8, IL-9, IL-10, IL-12, IL-13, IL-15, IL- 17, Eotaxin, bFGF-2, G-CSF, GM-CSF, IFN-γ, IP-10, MCP-1, MIP-1α, MIP-1β, PDGF-bb, RANTES, TNF, and VEGF) associated with Th1 and Th2 cytokine homeostasis. IL-10 and G-CSF levels were elevated in the asymptomatic group when compared with the healthy group (P=.031 and .041, resp.). The median ratios of IL-1β:5, IL-1β:10, IL-1β:G-CSF, IL-1β:Eotaxin, IL-12:G-CSF, IL-15:10, IL-17:G-CSF, IL-17:Eotaxin, TNF:IL-4, TNF:IL-5, and TNF:G-CSF were significantly different among the two groups. Thus, asymptomatic malaria carriage may be linked to circulating levels of IL-10 and G-CSF.